2016
DOI: 10.1007/978-3-319-44781-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dropout Learning Regarded as Ensemble Learning

Abstract: Deep learning is the state-of-the-art in fields such as visual object recognition and speech recognition. This learning uses a large number of layers and a huge number of units and connections. Therefore, overfitting is a serious problem with it, and the dropout which is a kind of regularization tool is used. However, in online learning, the effect of dropout is not well known. This paper presents our investigation on the effect of dropout in online learning. We analyzed the effect of dropout on convergence sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 8 publications
(20 reference statements)
1
19
0
Order By: Relevance
“…These subnetworks then form an ensemble of small networks. Making inference using a trained deep network is akin to using the ensemble mean to make predictions, which is more robust (Baldi & Sadowski, ; Hara et al, ); and (2) because connections are randomly blocked, neuron weights cannot adjust at the same time to cancel each other's effects to fit the target (Hinton, Srivastava, et al, ). The simultaneous adjustment, termed coadaptation, is a primary reason for overfitting.…”
Section: Basicsmentioning
confidence: 99%
“…These subnetworks then form an ensemble of small networks. Making inference using a trained deep network is akin to using the ensemble mean to make predictions, which is more robust (Baldi & Sadowski, ; Hara et al, ); and (2) because connections are randomly blocked, neuron weights cannot adjust at the same time to cancel each other's effects to fit the target (Hinton, Srivastava, et al, ). The simultaneous adjustment, termed coadaptation, is a primary reason for overfitting.…”
Section: Basicsmentioning
confidence: 99%
“…Once complete, an average of the discovered models was taken at test time and a performance increase was observed. Hara et al [16] proposed the idea that regularisation methods such as Dropout can be considered to be ensembling techniques. They showed that model accuracy can be improved by taking an average over a network with learned and unlearned units.…”
Section: Related Workmentioning
confidence: 99%
“…The work reported here is also clearly related to the full combination method of multi-band processing [21] where a neural network is trained on each combination of bands. In our case, however, it is not necessary to explicitly train 2 N (where N is the number of bands used) different networks, as dropout can be also regarded as an ensemble technique [22]. And given that the multi-band approach is a special case of multi-stream processing, the present study is also closely related to the multi-stream framework of Mallidi et al [23], which is dropping certain streams whilst training the network for band combination.…”
Section: Related Workmentioning
confidence: 99%